Sex differences in comorbidities and COVID-19 mortality–Report from the real-world data - Yoshida, Yilin; Wang, Jia; Zu, Yuanhao (Frontiers in Public Health, 2022)
Background: The differential effect of comorbidities on COVID-19 severe outcomes by sex has not been fully evaluated. Objective: To examine the association of major comorbidities and COVID-19 mortality in men and women separately. Methods: We performed a retrospective cohort analysis using a large electronic health record (EHR) database in the U.S. We included adult patients with a clinical diagnosis of COVID-19 who also had necessary information on demographics and comorbidities from January 1, 2016 to October 31, 2021. We defined comorbidities by the Charlson Comorbidity Index (CCI) using ICD-10 codes at or before the COVID-19 diagnosis. We conducted logistic regressions to compare the risk of death associated with comorbidities stratifying by sex. Results: A total of 121,342 patients were included in the final analysis. We found significant sex differences in the association between comorbidities and COVID-19 death. Specifically, moderate/severe liver disease, dementia, metastatic solid tumor, and heart failure and the increased number of comorbidities appeared to confer a greater magnitude of mortality risk in women compared to men. Conclusions: Our study suggests sex differences in the effect of comorbidities on COVID-19 mortality and highlights the importance of implementing sex-specific preventive or treatment approaches in patients with COVID-19.